The Potential of Oligochaeta as Intermediate Host of Myxosporea Parasite in Common Carp (Cyprinus carpio Linnaeus) - Yani Hadiroseyani (Jurnal Akuakultur Indonesia)
Three genera of oligochaeta, i.e. Branchiura sowerbyi, Limnodrillus sp. and Lumbriculus sp. were fed on spores of Myxobolus artus before predated to juvenile of Cyprinus carpio. Spores of myxosporean were found on the fish, which get Limnodrillus. But those spores show different characters from spores of M. artus.